Church Attendance and Religious change Pooled European dataset (CARPE) - F. Biolcati; V. Lomazzi; F. Molteni; M. Quandt; C. Vezzoni (Gesis, 2020)
The CARPE project has been developed to empirically address the religious change and secularization debate. The present data set contains aggregate survey-based estimates for the proportion of persons attending church, according to various frequency/probability thresholds. Further variables are sample shares of denominations, proportion female, average respondent age, proportions of rough educational attainment groups, and identifiers for country, year, and survey programme. The pooled dataset involves 45 European countries and spans the years 1973 to 2016, with variable density of coverage across the countries. Those countries are Albania, Austria, Armenia, Belgium, Bosnia Herzegovina, Bulgaria, Belarus, Croatia, Cyprus, Northern Cyprus, Czech Republic, Denmark, Estonia, Finland, France, Georgia, Germany, Greece, Hungary, Iceland, Ireland, Italy, Kosovo, Latvia, Lithuania, Luxembourg, Macedonia, Malta, Moldova, Montenegro, Netherlands, Norway, Poland, Portugal, Romania, Russian Federation, Serbia, Slovak Republic, Slovenia, Spain, Sweden, Switzerland, Turkey, Ukraine, United Kingdom. Estimates were derived from the individual-level data of the following survey programmes: • Eurobarometer (http://ec.europa.eu/public_opinion/), • European Social Survey (ESS), (http://www.europeansocialsurvey.org/), • European Values Study (EVS), (http://www.europeanvaluesstudy.eu/), • International Social Survey Programme (ISSP) (http://www.issp.org/), • World Values Survey (WVS) (http://www.worldvaluessurvey.org/)